2007
DOI: 10.21091/mppa.2007.3024
|View full text |Cite
|
Sign up to set email alerts
|

Body Physique and Prior Training Experience as Determinants of SEFIP Score for University Dancers

Abstract: The Self-Estimated Functional Inability because of Pain (SEFIP) questionnaire is a simple tool used to define the pain status in different body regions of performers in aesthetic sports. In this study we revalidated the SEFIP in a sample of nonprofessional female university dancers (n = 45; mean age, 22.3 yrs). The dancers were divided into two groups according to their previous experience in dance and aesthetic-based sports: experienced (n = 24) and nonexperienced (n = 21). SEFIP was measured before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Lower calf circumference was a predictor of higher SEFIP score at pre-training for the inexperienced group as well. 17 Liederbach and colleagues did not find any greater risk for ACL injury based on sex, style of dance, race, oral contraceptive use, or other intrinsic physiological variables. The investigators did observe that most ACL injuries occurred late in the day and in the season.…”
Section: Incidence Of and Risk Factors For Musculoskeletal Injury And...mentioning
confidence: 92%
See 3 more Smart Citations
“…Lower calf circumference was a predictor of higher SEFIP score at pre-training for the inexperienced group as well. 17 Liederbach and colleagues did not find any greater risk for ACL injury based on sex, style of dance, race, oral contraceptive use, or other intrinsic physiological variables. The investigators did observe that most ACL injuries occurred late in the day and in the season.…”
Section: Incidence Of and Risk Factors For Musculoskeletal Injury And...mentioning
confidence: 92%
“…Two studies focused on ankle injuries, 8,11 one on ACL injuries, 10 one on psychosocial factors as risk for injury, 18 and one on previous experience and body physique as determinants for SEFIP scores. 17 Schmitt and colleagues found no association between ankle proprioception test scores and ankle injury in German dance students. 8 Hiller and co-workers reported that a history of previous lateral ankle sprain was associated with an increased risk of future sprain of the contralateral ankle.…”
Section: Incidence Of and Risk Factors For Musculoskeletal Injury And...mentioning
confidence: 97%
See 2 more Smart Citations
“…The scale was shown to participants at 15 s intervals while their arm remained in the cold water to obtain the representative level of discomfort from zero (no pain) to ten (the maximal pain ever felt). The SEFIP (Self-Estimated Functional Inability Because of Pain questionnaire) was designed for dancers [ 34 , 35 ] in injury and pain research utilizing a body map to localise pain, whereby 16 body areas are rated on a 5-point Lickert scale. The short form 20 version of the PASS (Pain Anxiety Symptoms Scale) [ 36 , 37 ] assessed four subscales referred to as dimensions in pain research: cognitive anxiety, escape and avoidance, fear, and physiological anxiety.…”
Section: Methodsmentioning
confidence: 99%